Responses of Tree Species in Vermicompost and Vermileachate Incoporated-coal Mine Spoil - Durai, M.V.; Senthil Murugan, A. (Indian Forester, 2013)
The present investigation was carried out to record changes in physico-chemical properties of vermicomposted coal mine spoil and to find out promising species for its reclamation. Four dozes of vermi-compost and vermin-leachate and 3 dozes of vermin-leachate were applied per 150 kg of coal mine dumps. To each treatment, sand was incorporated @ 7.5kg, 15kg, 22.5kg, and 30kg to enhance spoil porosity. The results indicated that pH of the treated spoil was decreased. Ninety viable seeds of Acacia nilotica, Swietina mahogany, Dalbergio sissoo and Prosopis juliflora were sown in each treatment and each treatment replicated three times. Biometric parameters viz., germination, survival nd percentage, plant height and number of branches of seedlings were recorded at end of 2 month. Acacia nilotica was found to be most promising species for coal mine dumps spoil. Hence amendment of organic fertilizer leads to enhance spoil porosity, organic carbon for the better environment for the plantation of forest species in coal mine dumps.